Drug Overdoses During the COVID‐19 Pandemic Among Recently Homeless Individuals. (14th February 2022) - Liu, Michael; Richard, Lucie; Campitelli, Michael A.; Nisenbaum, Rosane; Dosani, Naheed; Dhalla, Irfan A.; Wadhera, Rishi K.; Shariff, Salimah Z.; Hwang, Stephen W.
Abstract: Aims: To examine how weekly rates of emergency department (ED) visits for drug overdoses changed among individuals with a recent history of homelessness (IRHH) and their housed counterparts during the pre‐pandemic, peak, and re‐opening periods of the first wave of the COVID‐19 pandemic, using corresponding weeks in 2019 as a historical control. Design: Population‐based retrospective cohort study conducted between September 30, 2018 and September 26, 2020. Setting: Ontario, Canada. Participants: A total of 38 617 IRHH, 15 022 369 housed individuals, and 186 858 low‐income housed individuals matched on age, sex, rurality, and comorbidity burden. Measurements: ED visits for drug overdoses of accidental and undetermined intent. Findings: Average rates of ED visits for drug overdoses between January and September 2020 were higher among IRHH compared with housed individuals (rate ratio [RR], 148.0; 95% CI, 142.7–153.5) and matched housed individuals (RR, 22.3; 95% CI, 20.7–24.0). ED visits for drug overdoses decreased across all groups by 20% during the peak period (March 17 to June 16, 2020) compared with corresponding weeks in 2019. During the re‐opening period (June 17 to September 26, 2020), rates of ED visits for drug overdoses were significantly higher among IRHH (RR, 1.56; 95% CI, 1.44–1.69), matched housed individuals (RR, 1.25; 95% CI, 1.08–1.46), and housed individuals relative to equivalent weeks in 2019 (RR, 1.07; 95% CI, 1.02–1.11). The relative increase in drug overdose ED visits among IRHH was larger compared with both matched housed individuals ( P = 0.01 for interaction between group and year) and housed individuals ( P < 0.001) during this period. Conclusions: Recently homeless individuals in Ontario, Canada experienced disproportionate increases in ED visits for drug overdoses during the re‐opening period of the COVID‐19 pandemic compared with housed people.